2021
DOI: 10.1186/s12904-021-00764-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing nurses’ intention to work in the oncology specialty: multi-institutional cross-sectional study

Abstract: Background Nursing care for terminally ill cancer patients is routinely provided by oncology nurses in Saudi Arabia. Shortages and retention of oncology nurses is an important concern for healthcare leaders. Objectives To identify and describe predictors of nurses’ intention toward working in the oncology specialty amongst three groups: undergraduate nursing students, oncology registered nurses and postgraduate oncology nursing students. In particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Concerns for patient safety due to high acuity and less-competent staff were noted to cause significant stress, as did the death of the pediatric patient, or multiple deaths in a short timeframe, especially when nurses were not able to adequately grieve due to organizational factors (time constraints, nurse/patient ratios, and multiple task demands). These findings are in line with additional studies which demonstrate that direct care for the patient with cancer (Alrasheedi et al, 2021; Barrett & Yates, 2002; Bond, 1994; Bourdeanu et al, 2020; Lagerlund et al, 2015) or the critically ill pediatric patient (Boyle & Bush, 2018; Dryden-Palmer et al, 2018; Flanders et al, 2020) place a significant psychological burden on nursing staff. While organizational factors are no doubt influential, it is the nature of the patient cohort that precipitates moral and ethical onus on nursing staff.…”
Section: Discussionsupporting
confidence: 81%
“…Concerns for patient safety due to high acuity and less-competent staff were noted to cause significant stress, as did the death of the pediatric patient, or multiple deaths in a short timeframe, especially when nurses were not able to adequately grieve due to organizational factors (time constraints, nurse/patient ratios, and multiple task demands). These findings are in line with additional studies which demonstrate that direct care for the patient with cancer (Alrasheedi et al, 2021; Barrett & Yates, 2002; Bond, 1994; Bourdeanu et al, 2020; Lagerlund et al, 2015) or the critically ill pediatric patient (Boyle & Bush, 2018; Dryden-Palmer et al, 2018; Flanders et al, 2020) place a significant psychological burden on nursing staff. While organizational factors are no doubt influential, it is the nature of the patient cohort that precipitates moral and ethical onus on nursing staff.…”
Section: Discussionsupporting
confidence: 81%
“…The modified version consisted of nine sections including quantitative and open-ended 2014). Related to level of education, postgraduate oncology nursing students had higher PCQN mean scores than oncology registered nurses without higher qualifications (Alrasheedi et al, 2021) providing evidence that PC education is an important factor influencing nurses' PC knowledge.…”
Section: ) the Modified Global Home Health Nursingmentioning
confidence: 90%
“…Similarly, research focused on nurses' PC knowledge in SA found higher mean PCQN scores were correlated with recently taken PC education (Aboshaiqah, 2019; Abudari et al, 2014). Related to level of education, postgraduate oncology nursing students had higher PCQN mean scores than oncology registered nurses without higher qualifications (Alrasheedi et al, 2021) providing evidence that PC education is an important factor influencing nurses' PC knowledge.…”
Section: Factors Influencing Home-based Pc Nursing Practicementioning
confidence: 99%
“…Two studies provide information about the nursing workforce, which primarily comprises foreign nationals. Alrasheedi et al 24 examined factors associated with nurses' and nursing students' intention to work in oncology in a sample of 444 participants from 5 major hospitals. The researchers assessed the relationship between PC knowledge, attitudes toward caring for dying patients, self-efficacy, and job satisfaction with intention to practice oncology nursing in the future.…”
Section: Studies Of the Nursing Workforcementioning
confidence: 99%